2011
DOI: 10.1021/bm200400s
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Copolymerization Kinetics of γ-Methyl-α-methylene-γ-butyrolactone (MeMBL)

Abstract: The propagation kinetics and copolymerization behavior of the biorenewable monomer γ-methyl-α-methylene-γ-butyrolactone (MeMBL) are studied using the pulsed laser polymerization (PLP)/size exclusion chromatography (SEC) technique. The propagation rate coefficient for MeMBL is 15% higher than that of its structural analogue, methyl methacrylate (MMA), with a similar activation energy of 21.8 kJ·mol(-1). When compared to MMA, MeMBL is preferentially incorporated into copolymers when reacted with styrene (ST), MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…The copolymerization reactivity ratios were higher for MBL compared to the comonomers. Similarly, higher copolymerization reactivity ratios were found also for MBL derivatives, γ-MMBL and β-MMBL, during their copolymerization with styrene and MMA (Pittman and Lee, 2003;Cockburn et al, 2010) and n-butyl acrylate (BA) (Cockburn et al, 2011). In addition to batch copolymerizations, a γ-MMBL was successfully used also in copolymerization with styrene in miniemulsion (Qi et al, 2008) and using stabilizer-free precipitation either in water (Qi et al, 2008) or in isoamyl acetate (Ramram et al, 2016) to form polymeric particles of size in the range of 50-200 or 600-2600 nm, respectively.…”
Section: Free Radical Polymerization Of Mbl Derivativesmentioning
confidence: 86%
“…The copolymerization reactivity ratios were higher for MBL compared to the comonomers. Similarly, higher copolymerization reactivity ratios were found also for MBL derivatives, γ-MMBL and β-MMBL, during their copolymerization with styrene and MMA (Pittman and Lee, 2003;Cockburn et al, 2010) and n-butyl acrylate (BA) (Cockburn et al, 2011). In addition to batch copolymerizations, a γ-MMBL was successfully used also in copolymerization with styrene in miniemulsion (Qi et al, 2008) and using stabilizer-free precipitation either in water (Qi et al, 2008) or in isoamyl acetate (Ramram et al, 2016) to form polymeric particles of size in the range of 50-200 or 600-2600 nm, respectively.…”
Section: Free Radical Polymerization Of Mbl Derivativesmentioning
confidence: 86%
“…The study of the free-radical copolymerizations of γ MMBL (M1) with M2, including styrene, MMA, and n-butyl acrylate (nBA), has found that, when (24) compared to MMA, γ MMBL is preferentially incorporated into copolymers when copolymerized with styrene, MMA, and nBA (44). The monomer reactivity ratios fit from bulk copolymerizations of γ MMBL with styrene, MMA, and nBA are r 1 = 0.80 ± 0.04 and r 2 = 0.34 ± 0.04 (styrene), r 1 = 3.0 ± 0.3 and r 2 = 0.33 ± 0.01 (MMA), and r 1 = 7.0 ± 2.0 and r 2 = 0.16 ± 0.03 (nBA), respectively.…”
Section: Polymerization Characteristics Of Mbl With Aibn In 1979mentioning
confidence: 99%
“…The polymerization of γ MMBL has not been studied extensively as compared to MBL; nevertheless, it has also been polymerized by free-radical emulsion polymerization (16,41) as well as radical, anionic, and GTP methods (42). Free-radical copolymerizations of γ MMBL with MMA and styrene have been investigated in detail through photoinitiation using the pulsed-laser polymerization/size-exclusion chromatography technique (43,44). Recently reported literature for the polymerization of γ MMBL included coordination polymerization with metallocene complexes (36,45), half-sandwich indenyl rare-earth metal dialkyls (46), ansarare-earth metal catalysts (27), and group 4 nonmetallocene benzyl complexes (47); GTP with bifunctional silicon propagators (48) and dinuclear silyliumenolate bifunctional catalysts (49); anionic polymerization with potassium salts (KH/Al(C 6 F 5 ) 3 ) (50); and zwitterionic polymerization with N-heterocyclic carbenes (51) and alane-based classical and frustrated Lewis pairs (52,53).…”
Section: Introductionmentioning
confidence: 99%
“…The IPUE model in conjunction with pulsed‐laser polymerization/size‐exclusion chromatography (PLP/SEC) has been successfully applied to characterize quite a few binary copolymer systems . However, the underlying assumptions of IPUE are not always strictly obeyed.…”
Section: Introductionmentioning
confidence: 99%